Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Produktivitas Kinerja Karyawan Pada PT Harrosa Darma Nusantara - Reihan Fadhil Syah Hanan; Enjang Suherman (CV. ITTC INDONESIA, 2024)
This study aims to analyze the influence of leadership style and work environment on employee performance productivity at PT Harossa Dharma Nusantara. Human resources are the main asset that significantly affects the development of the organization. Good leadership style and a comfortable work environment play important roles in optimizing employee potential and increasing productivity. The hypothesis analysis results show that leadership style and work environment contribute 96.1% to employee performance productivity, while other factors also have relevant impacts. The t-test confirms that leadership style and work environment have a significant influence on employee performance productivity at PT Harossa Dharma Nusantara.